Immunomodulatory Effects of 1,25-Dihydroxyvitamin D3 on Dendritic Cells Promote Induction of T Cell Hyporesponsiveness to Myelin-Derived Antigens - Wai-Ping Lee; Barbara Willekens; Patrick Cras; Herman Goossens; Eva Martínez-Cáceres; Zwi N. Berneman; Nathalie Cools (Journal of Immunology Research)
While emerging evidence indicates that dendritic cells (DC) play a central role in the pathogenesis of multiple sclerosis (MS), their modulation with immunoregulatory agents provides prospect as disease-modifying therapy. Our observations reveal that 1,25-dihydroxyvitamin D3 (1,25(OH)2D3) treatment of monocyte-derived DC results in a semimature phenotype and anti-inflammatory cytokine profile as compared to conventional DC, in both healthy controls and MS patients. Importantly, 1,25(OH)2D3-treated DC induce T cell hyporesponsiveness, as demonstrated in an allogeneic mixed leukocyte reaction. Next, following a freeze-thaw cycle, 1,25(OH)2D3-treated immature DC could be recovered with a 78% yield and 75% viability. Cryopreservation did not affect the expression of membrane markers by 1,25(OH)2D3-treated DC nor their capacity to induce T cell hyporesponsiveness. In addition, the T cell hyporesponsiveness induced by 1,25(OH)2D3-treated DC is antigen-specific and robust since T cells retain their capacity to respond to an unrelated antigen and do not reactivate upon rechallenge with fully mature conventional DC, respectively. These observations underline the clinical potential of tolerogenic DC (tolDC) to correct the immunological imbalance in MS. Furthermore, the feasibility to cryopreserve highly potent tolDC will, ultimately, contribute to the large-scale production and the widely applicable use of tolDC.